Patient Age, Sex, and Inflammatory Bowel Disease Phenotype Associate With Course of Primary Sclerosing Cholangitis - Weismüller, Tobias J; Trivedi, Palak J; Bergquist, Annika; Imam, Mohamad; Lenzen, Henrike; Ponsioen, Cyriel Y; Holm, Kristian; Gotthardt, Daniel; Färkkilä, Martti A; Marschall, Hanns-Ulrich; Thorburn, Douglas; Weersma, Rinse K; et al. (Gastroenterology (New York, N.Y. 1943), 2017)
Primary sclerosing cholangitis (PSC) is an orphan hepatobiliary disorder associated with inflammatory bowel disease (IBD). We aimed to estimate the risk of disease progression based on distinct clinical phenotypes in a large international cohort of patients with PSC. We performed a retrospective outcome analysis of patients diagnosed with PSC from 1980 through 2010 at 37 centers in Europe, North America, and Australia. For each patient, we collected data on sex, clinician-reported age at and date of PSC and IBD diagnoses, phenotypes of IBD and PSC, and date and indication of IBD-related surgeries. The primary and secondary endpoints were liver transplantation or death (LTD) and hepatopancreatobiliary malignancy, respectively. Cox proportional hazards models were applied to determine the effects of individual covariates on rates of clinical events, with time-to-event analysis ascertained through Kaplan-Meier estimates. Of the 7121 patients in the cohort, 2616 met the primary endpoint (median time to event of 14.5 years) and 721 developed hepatopancreatobiliary malignancy. The most common malignancy was cholangiocarcinoma (n = 594); patients of advanced age at diagnosis had an increased incidence compared with younger patients (incidence rate: 1.2 per 100 patient-years for patients younger than 20 years old, 6.0 per 100 patient-years for patients 21-30 years old, 9.0 per 100 patient-years for patients 31-40 years old, 14.0 per 100 patient-years for patients 41-50 years old, 15.2 per 100 patient-years for patients 51-60 years old, and 21.0 per 100 patient-years for patients older than 60 years). Of all patients with PSC studied, 65.5% were men, 89.8% had classical or large-duct disease, and 70.0% developed IBD at some point. Assessing the development of IBD as a time-dependent covariate, Crohn's disease and no IBD (both vs ulcerative colitis) were associated with a lower risk of LTD (unadjusted hazard ratio [HR], 0.62; P < .001 and HR, 0.90; P = .03, respectively) and malignancy (HR, 0.68; P = .008 and HR, 0.77; P = .004, respectively). Small-duct PSC was associated with a lower risk of LTD or malignancy compared with classic PSC (HR, 0.30 and HR, 0.15, respectively; both P < .001). Female sex was also associated with a lower risk of LTD or malignancy (HR, 0.88; P = .002 and HR, 0.68; P < .001, respectively). In multivariable analyses assessing the primary endpoint, small-duct PSC characterized a low-risk phenotype in both sexes (adjusted HR for men, 0.23; P < .001 and adjusted HR for women, 0.48; P = .003). Conversely, patients with ulcerative colitis had an increased risk of liver disease progression compared with patients with Crohn's disease (HR, 1.56; P < .001) or no IBD (HR, 1.15; P = .002). In an analysis of data from individual patients with PSC worldwide, we found significant variation in clinical course associated with age at diagnosis, sex, and ductal and IBD subtypes. The survival estimates provided might be used to estimate risk levels for patients with PSC and select patients for clinical trials.